2010
DOI: 10.1093/ejo/cjq021
|View full text |Cite
|
Sign up to set email alerts
|

Survey of congenitally missing teeth in orthodontic patients in Eastern Bavaria

Abstract: This retrospective study examined the occurrence of congenitally missing permanent teeth and the need for dental treatment in the Regensburg University Medical Centre of Eastern Bavaria. Using a dental administration software tool, a total of 1442 patients who presented for orthodontic treatment between 1994 and 2006 were identified. After exclusion of 89 patients with incomplete records, 1353 subjects (635 males and 718 females) remained for analysis. Of these, 1130 had no missing permanent teeth, 52 had clef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
78
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 17 publications
13
78
3
4
Order By: Relevance
“…geographic differences. 25,26 Hypodontia was more frequently found in females with no statistical difference, and this is agreeing with several studies, 13,[16][17][18]20,21,27 while Bäckman and Wahlin found significant difference between genders. 28 The higher prevalence of hypodontia in females may be due to biological differences and higher demands to aesthetic by females that make more orthodontic treatment need.…”
Section: Resultssupporting
confidence: 90%
“…geographic differences. 25,26 Hypodontia was more frequently found in females with no statistical difference, and this is agreeing with several studies, 13,[16][17][18]20,21,27 while Bäckman and Wahlin found significant difference between genders. 28 The higher prevalence of hypodontia in females may be due to biological differences and higher demands to aesthetic by females that make more orthodontic treatment need.…”
Section: Resultssupporting
confidence: 90%
“…[21617] However, a very high prevalence was reported in two German studies (12.6%)[16] and (11.3%)[2] when compared to this study result. Further, in Japanese orthodontic patients, a lower percentage value of 8.5% was noted,[11] when compared to the German study and higher than the results of our study.…”
Section: Discussioncontrasting
confidence: 75%
“…[291011161718] This wide range make the comparison of this study result very limited with other previous studies in addition to other contributing factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations